The Effect of Celebrity's Physical Attractiveness on The Buy Intention Among Young Consumers (Vallis Aurea, 2024)
Consumer behavior and factors affecting their buying behavior is one of the important issues in marketing and sales that many factors affect this process. Using celebrities as endorsers and their presence in advertisements is one of the effective factors in attracting customers. The present study investigated the effect of the apparent attractiveness of celebrities on the intention among young consumers. The answers of 410 Iranian young people, between 17 to 30 years, were collected and examined through the distribution of questionnaires on social networks. The Chi-Square test was used to examine the independence of the variables and the correlation coefficient was used to determine the type and direction of the relationship between the components.The results show that any physical attractiveness of celebrities is not significantly different in terms of gender between males and females and also showed that the physical attractiveness of celebrities has a positive and significant effect on the intention of young consumers to buy. The relationship between the questions and the type of celebrity impact on youth has also been investigated.